Escalating SARS-CoV-2 specific humoral immune response in rheumatoid arthritis patients and healthy controls - Nemeth, Dora; Vago, Hajnalka; Tothfalusi, Laszlo; Ulakcsai, Zsuzsanna; Becker, David; Szabo, Zsofia; Rojkovich, Bernadett; Gunkl-Toth, Lilla; Merkely, Bela; Nagy, Gyorgy (Frontiers in Immunology, 2024)
Background Immunocompromised patients are at particular risk of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection and previous findings suggest that the infection or vaccination induced immune response decreases over time. Our main goal was to investigate the SARS-CoV-2-specific immune response in rheumatoid arthritis patients and healthy controls over prolonged time. Methods The SARS-CoV-2-specific humoral immune response was measured by Elecsys Anti-SARS-CoV-2 Spike (S) immunoassay, and antibodies against SARS-CoV-2 nucleocapsid protein (NCP) were also evaluated by Euroimmun enzyme-linked immunosorbent assay (ELISA) test. The SARS-CoV-2-specific T-cell response was detected by an IFN- γ release assay. Results We prospectively enrolled 84 patients diagnosed with rheumatoid arthritis (RA) and 43 healthy controls in our longitudinal study. Our findings demonstrate that RA patients had significantly lower anti-S antibody response and reduced SARS-CoV-2-specific T-cell response compared to healthy controls (p<0.01 for healthy controls, p<0.001 for RA patients). Furthermore, our results present evidence of a notable increase in the SARS-CoV-2-specific humoral immune response during the follow-up period in both study groups (p<0.05 for healthy volunteers, p<0.0001 for RA patients, rank-sum test). Participants who were vaccinated against Coronavirus disease-19 (COVID-19) during the interim period had 2.72 (CI 95%: 1.25–5.95, p<0.05) times higher anti-S levels compared to those who were not vaccinated during this period. Additionally, individuals with a confirmed SARS-CoV-2 infection exhibited 2.1 times higher (CI 95%: 1.31–3.37, p<0.01) anti-S levels compared to those who were not infected during the interim period. It is worth noting that patients treated with targeted therapy had 52% (CI 95%: 0.25–0.94, p<0.05) lower anti-S levels compared to matched patients who did not receive targeted therapy. Concerning the SARS-CoV-2-specific T-cell response, our findings revealed that its level had not changed substantially in the study groups. Conclusion Our present data revealed that the level of SARS-CoV-2-specific humoral immune response is actually higher, and the SARS-CoV-2-specific T-cell response remained at the same level over time in both study groups. This heightened humoral response, the nearly permanent SARS-CoV-2-specific T-cell response and the coexistence of different SARS-CoV-2 variants within the population, might be contributing to the decline in severe COVID-19 cases.